2019
DOI: 10.1002/ecy.2759
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing community structure subject to incomplete sampling: hierarchical community model vs. canonical ordinations

Abstract: Citation: Yamaura, Y., F. G. Blanchet, and M. Higa. 2019. Analyzing community structure subject to incomplete sampling: hierarchical community model vs. canonical ordinations. Ecology 100(8):Abstract. Recently developing hierarchical community models (HCMs) accounting for incomplete sampling are promising approaches to understand community organization. However, pros and cons of incorporating incomplete sampling in the analysis and related design issues remain unknown. In this study, we compared HCM and canoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 60 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…Indeed, Yamamura, Blanchet, and Higa () recently demonstrated performance differences between dbRDAs with different distance metrics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Yamamura, Blanchet, and Higa () recently demonstrated performance differences between dbRDAs with different distance metrics.…”
Section: Discussionmentioning
confidence: 99%
“…Yamamura et al () compared a Bayesian hierarchical model (BHM) with dbRDA focusing on the impact of incomplete and unequal sampling. They found that the BHM and dbRDA estimated the dependence of the species abundances on environmental variables similarly well.…”
Section: Discussionmentioning
confidence: 99%